Olena Pavlivna Baburkina - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
May 11, 2020 marked the 60th anniversary of the birth of Doctor of Medical Sciences, Head of the Department of Scientific and Medical Information of the State Institution «Sytenko Institute of Spine and Joint Pathology of the National Academy of Medical Sciences of Ukraine» to Baburkina Olena Pavlivna.